A Broadband High-Efficiency Hybrid Continuous Inverse Power Amplifier Based on Extended Admittance Space - Ni, Chun; Wang, Hui; Liu, Jing; Chen, Mingsheng; Zhang, Zhongxiang; Zhang, Liang; Zhu, Jiabing; Wu, Xianliang (Frontiers in Physics, 2021)
A novel hybrid continuous inverse power amplifier (PA) that is constituted by a continuum of PA modes from the continuous inverse class-F to the continuous inverse class-B/J is proposed, and a detailed mathematical analysis is presented. The fundamental and second harmonic admittance spaces of the hybrid PA proposed in this article are analyzed mathematically. By introducing the phase shift parameter into the current waveform formula of the hybrid continuous inverse PA, the design space of the fundamental and second harmonic admittance is expanded, further increasing the operating bandwidth. The efficiency of the amplifier under different parameter conditions is calculated. In order to verify this method, a broadband high-efficiency PA is designed and fabricated. The drain voltage and current waveforms of the amplifier are extracted for analysis. The experimental measured results show a 60.7–71.5% drain efficiency across the frequency band of 0.5–2.5 GHz (133% bandwidth), and the designed PA can obtain an 11.8–13.9 dB gain in the interesting frequency range. The measured results are confirmed to be in good agreement with theory and simulations.